Effect of Soil-Applied Metabolic Modulators on the Accumulation of Specialized Metabolites in Chelidonium majus L. - Maria Stasińska-Jakubas; Sławomir Dresler; Maciej Strzemski; Magdalena Wójciak; Katarzyna Rubinowska; Barbara Hawrylak-Nowak (Molecules)
Various metabolic modulators have been widely used in recent years to increase the accumulation of desired secondary metabolites in medicinal plants, although most studies to date have focused on in vitro systems. Although simpler and cheaper, their potential application in vivo is still limited. Therefore, the aim of this study was to compare the effect of three chemically different elicitors (150 mg/L chitosan lactate—ChL; 10 mg/L selenium as selenite—Se; 100 mg/L salicylic acid—SA) applied to the soil substrate on some aspects of the secondary metabolism and physiological responses of Chelidonium majus L. Using HPLC-DAD, six isoquinoline alkaloids were identified and quantified in shoot extracts. LC-ESI-TOF-MS analysis confirmed the molecular identity of all target alkaloids, supporting the identification. The strongest stimulatory effect on the accumulation of protopine, berberine, and allocryptopine was observed with the Se and SA treatment, whereas ChL was less effective. In turn, the dominant alkaloids (coptisine and chelidonine) remained unaffected. There was also an increase in total phenolic compounds, but not in soluble flavonols. The elicitor treatments caused an increase in the antioxidant activity of the plant extracts obtained. Regardless of the metabolic modulator type, the strongest effect was generally observed on days 7 and 10 after application. No visual signs of toxicity and no effect on shoot biomass were found, although some elicitor-induced changes in the oxidative status (increased H2O2 accumulation and enhanced lipid peroxidation) and free proline levels in leaves were observed. We suggest that Se or SA can be applied to C. majus grown in a controlled pot culture to obtain high-quality raw material and extracts with increased contents of valuable specialized metabolites and enhanced antioxidant capacity.